Biology and significance of alpha‐fetoprotein in hepatocellular carcinoma - Galle, Peter R.; Foerster, Friedrich; Kudo, Masatoshi; Chan, Stephen L.; Llovet, Josep M.; Qin, Shukui; Schelman, William R.; Chintharlapalli, Sudhakar; Abada, Paolo B.; Sherman, Morris; Zhu, Andrew X. (Liver international, 2019)
Hepatocellular carcinoma (HCC) is one of the most common causes of cancer‐related deaths globally due, in part, to the majority of patients being diagnosed with intermediate or advanced stage disease. Our increased understanding of the heterogeneous molecular pathogenesis of HCC has led to significant developments in novel targeted therapies. Despite these advances, there remains a high unmet need for new treatment options. HCC is a complex disease with multiple pathogenic mechanisms caused by a variety of risk factors, making it difficult to characterize with a single biomarker. In fact, numerous biomarkers have been studied in HCC, but alpha‐fetoprotein (AFP) remains the most widely used and accepted serum marker since its discovery over 60 years ago. This review summarizes the most relevant studies associated with the regulation of AFP at the gene and protein levels; the pathophysiology of AFP as a pro‐proliferative protein; and the correlation of AFP with molecular HCC subclasses, the vascular endothelial growth factor pathway and angiogenesis. Also described are the historical and current uses of AFP for screening and surveillance, diagnosis, its utility as a prognostic and predictive biomarker and its role as a tumour antigen in HCC. Taken together, these data demonstrate the relevance of AFP for patients with HCC and identify several remaining questions that will benefit from future research.